Rancang bangun thermocouple data logger multichannel berbasis Arduino Mega 2560 - Joni, Joni; Efendi, Rustam (Universitas Muhammadiyah Metro, 2024)
Measuring temperature using a data logger is a suitable choice for temperature measurements of an object. The availability of Arduino as a microcontroller has become a preference for developments, especially in temperature measurement devices. One temperature sensor that has good accuracy is the Adafruit MAX31856. This research aims to design a low-cost temperature data logger. The method used in this research is the design and build method. The results of this research show that the temperature data logger works well. This is indicated by the close correlation of the measurement results from each sensor. This applies to measurements of heated water as well as water taken from the dispenser.